La inteligencia emocional y el desarrollo de los principios del buen vivir, en los niños de cuarto año de Educación Básica, paralelo “B” de la escuela Fiscal Mixta “General Lavalle”, del cantón Riobamba, barrio Lizarzaburu de la ciudad de Riobamba provincia de Chimborazo periodo 2015-2016 - Silva Castillo, Laura Priscila (2016)
This research aims to identify the level of emotional intelligence in children of fourth year of basic education, parallel" B" at "General Lavalle " public school in Riobamba canton, Lizarzaburu neighborhood, Riobamba city, Chimborazo province, period 2015-2016. So students were helped to make decisions, to have a more critical thinking about themselves and their surroundings, this research could identify the level of self-esteem with the principles and convictions that have to society and respect for the good life with others that helps the possibility of having a better education with principles and values set for improvement their education, they are aware of emotions where it is found personality problems and emotional development for themselves. For drawing up this research it has been given different guidelines that have given the solution of this problem, so everything about the development of this topic is mentioned below: This means that the primary basis of this work is the framework where the problem statement was established, the formulation of the problem, objectives and justification were determined to identify the theoretical foundation and operationalization of variables, the methodological framework was developed where scientific methods such us inductive and deductive were applied, the research type is explanatory, the research design was field and documentary, the population of 25 children was determined, also referring to the technique and research instruments the test was performed, and then it was made a statistical analysis of the results that were obtained with students´ participation, conclusions and recommendations based mainly on the issue of the problem were shown.